Measuring and communicating the effects of traffic incident management improvements. - Margiotta, Richard A.; Voorhies, Kenny; Lomas, Tim (Research results digest (National Cooperative Highway Research Program), 2004)
"This digest presents the results of NCHRP Project 20-7/Task 173, 'Measuring and communicating the effects of incident management improvements.' The research team (composed of Richard Margiotta and Kenny Voorhies ... and Tim Lomas ...) ..."